The Role of Brand Equity, Digital Marketing, Customer Experience, and Social Media Engagement on Consumer Purchase Intention on Tiktok Shop Application - Wahyuni, Ira; Arifiansyah, Rully; Meidasari M, Evi; Siskawati, Isna (IJBLE Scientific Publications Community Inc., 2024)
This study explores the role of brand equity, digital marketing, customer experience, and social media engagement in influencing consumer purchase intention on the TikTok Shop platform. Utilizing a quantitative research design, data were collected from 400 TikTok users engaged with the platform. The findings reveal significant positive relationships between all constructs and purchase intention, with customer experience identified as the strongest predictor. The results underscore the importance of building strong brand identities, implementing targeted digital marketing strategies, and enhancing customer experiences to drive consumer engagement and sales. Furthermore, active social media engagement is crucial for fostering relationships with consumers and increasing purchase intentions. This research contributes to the understanding of consumer behavior in social commerce and provides practical implications for marketers aiming to succeed in the rapidly evolving digital landscape.